Molecular pathogenesis of Wilson and Menkes disease: correlation of mutations with molecular defects and disease phenotypes. Issue 11 (23rd August 2007) - de Bie, P; Muller, P; Wijmenga, C; Klomp, L W J
Abstract : The trace metal copper is essential for a variety of biological processes, but extremely toxic when present in excessive amounts. Therefore, concentrations of this metal in the body are kept under tight control. Central regulators of cellular copper metabolism are the copper-transporting P-type ATPases ATP7A and ATP7B. Mutations in ATP7A or ATP7B disrupt the homeostatic copper balance, resulting in copper deficiency (Menkes disease) or copper overload (Wilson disease), respectively. ATP7A and ATP7B exert their functions in copper transport through a variety of interdependent mechanisms and regulatory events, including their catalytic ATPase activity, copper-induced trafficking, post-translational modifications and protein–protein interactions. This paper reviews the extensive efforts that have been undertaken over the past few years to dissect and characterise these mechanisms, and how these are affected in Menkes and Wilson disease. As both disorders are characterised by an extensive clinical heterogeneity, we will discus how the underlying genetic defects correlate with the molecular functions of ATP7A and ATP7B and with the clinical expression of these disorders.